2004
DOI: 10.1063/1.1828216
|View full text |Cite
|
Sign up to set email alerts
|

Antimony orthophosphate glasses with large nonlinear refractive indices, low two-photon absorption coefficients, and ultrafast response

Abstract: Antimony glasses based on the composition Sb 2 O 3 -SbPO 4 were prepared and characterized. The samples present high refractive index, good transmission from 380 to 2000 nm, and high thermal stability. The nonlinear refractive index, n 2 , of the samples was studied using the optical Kerr shutter technique at 800 nm. The third-order correlation signals between pump and probe pulses indicate ultrafast response ͑Ͻ100 fs͒ for all compositions. Enhancement of n 2 was observed by adding lead oxide to the Sb 2 O 3 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The phonon energy of Sb–O bond in SbO 3 structural units (~600‐700 cm −1 ) is comparatively low. Because of this reason, Sb 2 O 3 ‐based glasses posses larger values of linear and non‐linear refractive indices when compared with those of other glass materials. As a result, there is a possibility for modulation of their optical constants, (viz., refractive index, n , and absorption coefficient, α ) under electromagnetic irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The phonon energy of Sb–O bond in SbO 3 structural units (~600‐700 cm −1 ) is comparatively low. Because of this reason, Sb 2 O 3 ‐based glasses posses larger values of linear and non‐linear refractive indices when compared with those of other glass materials. As a result, there is a possibility for modulation of their optical constants, (viz., refractive index, n , and absorption coefficient, α ) under electromagnetic irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The development of nonlinear (NL) photonic devices is motivating the discovery of new optical glasses useful for all-optical switching, optical limiting, lasers, and infrared technologies. Among the glass families known chalcogenides , and antimony based glasses , are examples of materials having appropriate characteristics for photonic devices according to various authors. However, heavy-metal-oxides (HMO) such as Bi 2 O 3 , WO 3 , Sb 2 O 3 , and PbO are subject of intense current research because their NL optical properties can be tailored using appropriate concentrations of elements with large hyperpolarizability and extended infrared transmittance. ,− On the other hand, phosphate glasses, transparent from the ultraviolet to 5 μm, have been increasingly applied in photonics due to their interesting properties, such as low glass transition temperature, T g , and high thermal expansion coefficient that allows easy fabrication of optical fibers. , Among the phosphate glasses, those based on sodium-polyphosphate are frequently used as host matrices because of their high vitrifying ability and unusual capability to dissolve large amounts of other glass formers, modifiers, or intermediate compounds without reduction of glass forming ability .…”
Section: Introductionmentioning
confidence: 99%
“…17 Further, Lin et al 65 67 evaluated the optical nonlinearity of HMO glasses through the optical Kerr gate method and found that the temporal response was faster than 350 fs. Falcaõ-Filho et al 27 measured the response time of antimony orthophosphate glasses, in which the correlation signals between pump and probe pulses represent ultrafast response (<100 fs) for all glass compositions. Their results clearly demonstrated that the observed nonlinearity arises predominantly from electronic polarization.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…26 Terashima et al 17 studied the Sb 2 O 3 −B 2 O 3 glasses and reported that the thirdorder nonlinear optical susceptibility [χ (3) ] of binary borate glasses is enhanced with increasing Sb 2 O 3 content. Falcaõ-Filho et al 27 demonstrated that the antimony orthophosphate glasses possess excellent nonlinear refractive index at 800 nm. Very recently, it has been observed that sodium borate glasses with a small amount (2 mol %) of antimony resulted in a small two-photon absorption (2PA) at 800 nm in femtosecond (fs) regime.…”
Section: Introductionmentioning
confidence: 99%